2010
DOI: 10.1172/jci40676
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphin deletion protects mice from inflammation-induced colon carcinogenesis and alters stem cell niche myofibroblast secretion

Abstract: Epithelial-mesenchymal interactions regulate normal gut epithelial homeostasis and have a putative role in inflammatory bowel disease and colon cancer pathogenesis. Epimorphin is a mesenchymal and myofibroblast protein with antiproliferative, promorphogenic effects in intestinal epithelium. We previously showed that deletion of epimorphin partially protects mice from acute colitis, associated with an increase in crypt cell proliferation. Here we explored the potential therapeutic utility of modulating epimorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 64 publications
3
66
0
Order By: Relevance
“…To determine BrdUrd incorporation, sections were stained using a BrdUrd In Situ Detection Kit (BD Pharmingen) according to the manufacturer's recommendations. Cell proliferation was assessed as described previously (19).…”
Section: Cell-proliferation Assay In Vivomentioning
confidence: 99%
“…To determine BrdUrd incorporation, sections were stained using a BrdUrd In Situ Detection Kit (BD Pharmingen) according to the manufacturer's recommendations. Cell proliferation was assessed as described previously (19).…”
Section: Cell-proliferation Assay In Vivomentioning
confidence: 99%
“…The technique described has been successfully used by the authors to establish primary murine colonic myofibroblasts 7 and further adapted for establishment of murine 6 and human myofibroblast-like esophageal stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the role of myofibroblasts in regulating proliferation and carcinogenesis of the gut epithelium, we have studied epimorphin (Epim), a member of the syntaxin family of vesicle-docking proteins expressed in gut myofibroblasts (10,33,35). Syntaxins are SNARE complex structural proteins that are required for membrane fusion events.…”
mentioning
confidence: 99%
“…One of the best studied, syntaxin 1, functions as part of a target or t-SNARE complex to mediate neurotransmitter release in synapses (11). We have shown that Epim, or syntaxin 2, plays a role in regulating myofibroblast secretion of growth factors and cytokines (33). Epim is also unique among the syntaxins; in addition to its intracellular function as a vesicle-docking protein that regulates cellular secretion, it also has an extracellular location (6,12,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation